Analyzing the Cross-Linking of HNBR Utilizing Peroxide and Triazine Compounds - Mammadov, A.Kh.; Khankishiyeva, R.F.; Akhundzada, H.N.; Salehov, A.Kh. (Physics and Chemistry of Solid State, 2025)
Investigated the role of polymer peroxide (1,4-bis-tret butyl peroxy isopropyl benzene) and triazine compounds (6-bis-trichloromethyl sym-triazine, 2-phenyl-4) under heating in hydrogenated butadiene nitrile rubber (HNBR) systems. The changes in HNBR's molecular structure when polymer peroxides and triazine compounds are present, as demonstrated by spectral, physical, and chemical methods of analysis: Decided the energy of yield and the rise of cross-connecting thickness of the matrix HNBR for each researched framework rely upon time. It is shown that cross connecting of the HNBR with peroxide polymers happens by an extreme sort. The study investigated the effects of polymer peroxides and triazine compounds on the molecular structure of hydrogenated butadiene nitrile rubber (HBNR) under heating, determined the kinetics of yield and the emergence of cross-linking density of the HBNR for each system studied, and showed that crosslinking occurs by a radical type.